Content of ensuring the integration of pedagogical and information technologies in higher pedagogical education (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, the content, legislative basis and current situation of ensuring the integration of pedagogical and information technologies in improving the methodological training of future teachers and thereby developing a potential pedagogue are researched.